Pembelajaran Matematika Materi Pembagian Menggunakan Bar Diagram dan Leftover Game Board - Isti Khomaria; Babang Robandi (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2023)
Pedagogy mastery for primary school teachers is a key to delivering meaningful learning yet fun. Teachers should know the best methods for students to engage in learning activities that enrich their learning experience. Making mathematics way more fun could be formulated by adopting such a visual model to uplift students’ understanding of mathematics concepts. Sharpening students’ mathematics thinking could also be modeled as a game. This study aimed to describe how fruitful teaching division in mathematics is for fourth grade using a bar diagram and leftover game board. This has been researched with a descriptive qualitative approach using the case study method. The subjects of this study are eight students in grade four. The data sources were collected from students' activity during the learning process observation sheet, students’ worksheets, and students’ interview sheets. The data was analyzed through data collection, data reduction, data display, and conclusion. This study revealed that teaching division using a bar diagram could ease students’ lack of dividing numbers with two number digits and leftover game board activity could make students come over with positive attitudes towards mathematics, such as fascination, pleasure, and passion, engage in healthy academic competition during in-class activities.